Measurement of Depressive Symptoms in Patients with Cancer in Nineveh Governorate - Yasir Netham Aldeen Majeed; Wa'ad Mohammed Rajab (College of Nursing,University of Mosul, 2017)
Background and aim: Cancer is the second leading cause of death among adults. Patients with cancer suffer from different psychiatric and mental problems due to their disease. However, the aim of this study is to assess depressive symptoms in adult patients with cancer, according to the variables (gender, type of cancer and stage of cancer). Materials and method: A descriptive study design was adopted in the present study. The subjects consist of (306) patients with cancer and age group between (19 more than 70) years. The data were collected from Nineveh Governorate, and carried out in oncology and nuclear medicine specialist and Ibn-Sina Teaching Hospital in Mosul, during a period from 5th December 2012 to 5th of April 2013. Both the scales International Beck Depression Inventory - Scale the scale strategies life events adopted it the study. Results: The findings of the study indicated that there are significant statistical differences between depressive symptoms with regarding (age group, religion, educational levels, socioeconomic status, type of cancer, time since diagnosis and stage of cancer). Recommendations: the study has recommended to encourage the patients with cancer, using strategies of confrontation and challenge, and based spiritual to reduce depressive symptoms for them. Keywords: depressive symptoms, patients, Cancer